Jejak Sejarah yang Hidup: Dedikasi kepada Masyarakat melalui Pelestarian Makam Sultanah Nahrasiyah - Razali; Sundana, Lina; Nurfadilla (Yayasan Kawanad, 2024)
The Tomb of Sultanah Nahrasiyah in North Aceh stands as a testament to the historical prominence of Aceh. This study aims to examine and analyze the inscriptions engraved on the tombstones of Sultanah Nahrasiyah. The methodology consists of meticulous observation and documentation, followed by an in-depth analysis of the tombstone inscriptions. The initial stage involves a historical review of Sultanah Nahrasiyah's leadership. Subsequently, the study emphasizes the participation of female students in the examination and analysis of the inscriptions within the tomb complex. The Arabic inscriptions are analyzed with reference to the Quran, supported by insights from a historical guide who serves as the tomb's custodian. The findings suggest that understanding the historical significance of Sultanah Nahrasiyah's tomb is instrumental in fostering historical awareness and serves as a foundation for applying historical principles to contemporary contexts. This initiative is expected to deepen academic understanding of Sultanah Nahrasiyah's legacy.